Assessment of an Isolation Condenser of an Integral Reactor in View of Uncertainties in Engineering Parameters. (2nd December 2010) - Lorenzo, G.; Zanocco, P.; Giménez, M.; Marquès, M.; Iooss, B.; Bolado Lavín, R.; Pierro, F.; Galassi, G.; D'Auria, F.; Burgazzi, L.
Abstract : RMPS methodology is used for estimating the uncertainties in the fulfillment of a target related with the design of the isolation condenser of a "CAREM-like" integral reactor. The passive-system assessment is made on a basis of a loss of heat sink transient. Given this scenario, the safety function is to remove the core decay heat after the actuation of the shutdown system, thus reducing the primary system pressure and leading the plant to a safe condition. The design target to evaluate is the avoidance of the RPV safety valves opening. In order to accomplish the evaluation, the following RMPS steps were followed: system identification, system modeling, characterization of TH phenomena, direct Monte Carlo simulation, sensitivity analysis, and quantitative reliability estimation. As main outcomes, a ranking of parameters' importance and an estimate of the failure probability, from a design target point of view, were achieved by sensitivity analysis and Monte Carlo simulations based on a response surface model.